Pengaruh Model Project Based Learning terhadap Kemampuan Menulis Teks Berita Siswa Kelas XI SMAN 2 Kota Bengkulu - Astuti, Maria Winda Puji; Arono, Arono; Ariesta, Ria (Jurnal Korpus, 2025)
The study was named, "The Influence of the Project Based Learning (Pjbl) Model on the Ability to Write News Text for Class XI of State High School 2 Bengkulu City" . The purpose of this study is to examine how the project-based learning paradigm affects students' capacity to compose news articles. This study employed a quantitative methodology and a kind of experiment with methods. by learning observation, student response’s questionnaire, and the write news text’s assessment. The learning process lasted for six meetings. Based on the observation and student response’s questionnaire results, an average total score was obtained 72,85 included in the “Good” categorial. Besides that, from the results of the write news text’s assessment, an average total score was obtained 78,7 included in “Good” categorial. Simple linear regression is used for hypothesis testing; the results show a t-count of 5.379 and a t-table of 2.045, with degrees of freedom (df) of 29 and a significance threshold of α = 0.05. The t-count > t-table value. Then based on the criteria for testing the hypothesis H0 is rejected and Ha is accepted. Therefore, it can be concluded that there is a significant effect of using the project-based learning model on the ability to write a news text, based on the results that have been obtained.